Die Arten der Gattung Oegoconia Stainton, 1854 in Deutschland und ihre Verbreitung in Ostdeutschland (Lepidoptera: Autostichidae). - Sutter, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 2003)
The genus Oegoconia is represented in the East German states by three species. The records are listed, records from other parts of Germany are added. O. novimundi Busck, 1915 is recorded for the first time from Germany (Baden-Württemberg). A key to all five species of Germany is provided.